1988
DOI: 10.1002/eji.1830181010
|View full text |Cite
|
Sign up to set email alerts
|

Functional discrimination between interleukin 6 and interleukin 1

Abstract: In this study we have investigated the specificity of bioassays in which interleukin (IL) 1 and/or IL 6 are active. The thymocyte assay cannot be used to discriminate between IL 1 and IL 6; both monokines are active in this assay. Moreover the detection limit for both IL 1 and IL 6 is around 100 pg/ml. IL 6 activity can be measured with a murine hybridoma cell line (B9). The detection limit for human as well as murine IL 6 is about 0.5 pg/ml. The assay is specific for IL 6 and is not influenced by a variety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
173
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 408 publications
(175 citation statements)
references
References 35 publications
1
173
0
Order By: Relevance
“…In the absence of antibodies to canine IL-6, the possibility that other factors contribute to the proliferation of B9 cells cannot be ruled out; however, the activity is most likely to be due to IL-6. On testing a number of human and murine cytokines, alone and in combination (IL-la, IL-I@, IL-2, IL-3, IL-4, TNFa, IFNy, and GM-CSF), Helle et a1 (11) found that only murine IL-4 showed any activity toward B9 cells, and that IL-4 was only 0.02% as active as IL-6. There are many possible sources of the IL-6 present in synovial fluid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of antibodies to canine IL-6, the possibility that other factors contribute to the proliferation of B9 cells cannot be ruled out; however, the activity is most likely to be due to IL-6. On testing a number of human and murine cytokines, alone and in combination (IL-la, IL-I@, IL-2, IL-3, IL-4, TNFa, IFNy, and GM-CSF), Helle et a1 (11) found that only murine IL-4 showed any activity toward B9 cells, and that IL-4 was only 0.02% as active as IL-6. There are many possible sources of the IL-6 present in synovial fluid.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 was measured by the B9 assay (11). Briefly, B9 murine hybridoma cells (5,00O/well) were cultured in 96-well flat-bottom microtiter plates in RPMI 1640 containing 5% fetal calf serum (FCS), 100 units/ml penicillin, and 100 pg/ml streptomycin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…B9 cells are insensitive to IL-la, IL-lP, IL-2, IL-3, IL-4, tumor necrosis factor a, interferon-y, and granulocytemacrophage colony-stimulating factor (17). In previous control experiments, the IL-6 activity in the cartilage culture media was assessed by the addition (in the B9 assay) of antibodies raised against highly purified rHuIL-6 (8).…”
Section: Methodsmentioning
confidence: 99%
“…Immediately after death blood was taken by cardiac puncture. The IL 6 concen trations in the sera obtained were measured using the B-9 cell line [5], and IL1 concentrations were measured using D10.G4.1 cells [13], the D10(N4)M subclone; both assays have been described in detail [14]. Similarly, serum concentra tions of IL 6 and IL 1 were measured after an i.p.…”
Section: Pharmacokinetics Of Ril 6 and Ril 1 And Induction Of Ilmentioning
confidence: 99%